2015
DOI: 10.5812/aapm.24837
|View full text |Cite
|
Sign up to set email alerts
|

Premedication With Oral Pregabalin for the Prevention of Acute Postsurgical Pain in Coronary Artery Bypass Surgery

Abstract: Background:For coronary artery bypass grafting (CABG) sternotomy should be performed. The pain after surgery is severe and requires medical intervention. Use of the analgesics is limited by their side effects and studies suggest that prevention with some medications before surgery is effective in controlling the postoperative pain.Objectives:We investigated the efficacy of pregabalin administration before surgery in the treatment of acute postoperative pain after CABG surgery.Patients and Methods:Sixty patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…Pregabalin has been used in different types of surgery and published clinical studies suggest that chronic pain may be reduced in patients who receive perioperative pregabalin [ 24 , 26 ], but data on the role of pregabalin in cardiac surgery are limited: Ziyaeifard et al [ 34 ] reported that a single preoperative dose of pregabalin 150 mg significantly reduced pain but had no effect on morphine consumption after elective CABG surgery, whereas Joshi and Jagadeesh reported that one pregabalin dose before and one daily pregabalin dose for two days after surgery reduced pain scores and tramadol consumption for 36 hours but had no effect on chronic postoperative pain in patients undergoing off-pump coronary artery bypass (OPCAB) surgery [ 35 ]. However, a prospective clinical trial by Pesonen et al showed that although perioperative pregabalin significantly reduced perioperative oxycodone consumption and the incidence of confusion, it increased the time to extubation in elderly patients undergoing cardiac surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin has been used in different types of surgery and published clinical studies suggest that chronic pain may be reduced in patients who receive perioperative pregabalin [ 24 , 26 ], but data on the role of pregabalin in cardiac surgery are limited: Ziyaeifard et al [ 34 ] reported that a single preoperative dose of pregabalin 150 mg significantly reduced pain but had no effect on morphine consumption after elective CABG surgery, whereas Joshi and Jagadeesh reported that one pregabalin dose before and one daily pregabalin dose for two days after surgery reduced pain scores and tramadol consumption for 36 hours but had no effect on chronic postoperative pain in patients undergoing off-pump coronary artery bypass (OPCAB) surgery [ 35 ]. However, a prospective clinical trial by Pesonen et al showed that although perioperative pregabalin significantly reduced perioperative oxycodone consumption and the incidence of confusion, it increased the time to extubation in elderly patients undergoing cardiac surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, administration of 150 mg of pregabalin prior to inducting anesthesia reduced pain scores and opioid consumption after hysterectomy 16. With pregabalin 150 mg prior to myocardial revascularization surgery, there was a decrease in pain intensity after 4, 12, and 24 hours 17. A systematic review showed that a single preoperative dose of 100–300 mg was effective, with no difference between doses 5…”
Section: Discussionmentioning
confidence: 99%
“…43 44 The present study was designed with the primary aim of examining whether the addition of pregabalin to a perioperative THA analgesic regimen (which includes spinal anaesthesia and perioperative celecoxib) while in hospital and for 1 week postdischarge improves pain and functional outcomes up to 3 months after surgery. The present study did not find significant differences between pregabalin and placebo groups in the primary measures of function (both physical and patient reported) at 6 weeks or 3 months after THA (Table 2).…”
Section: Discussionmentioning
confidence: 99%